Fungal Infection Associated with denture (Mustansiria Dental Journal, 2018)
Candida is a genus of yeast .Many species of this genus are symbiont of animalshost including humans. While usually living as commensally in oral cavity, somecandida can cause disease .The most significant member of the genus is candidaalbicans which can cause infection called candidiasis or thrush especially in elderlydenture wearers.So the denture seems to be frequently the sources of fungal infection.The current study aimed to determine the fungal prevalence rate in oral cavityamong denture wearers patients in comparison to those without dentures and also todetermine the local risk factors includes trauma due to ill fitting denture, nocturnalwear of the denture, heavy smoking and the age of the denture.The result of this study showed that the prime etiology of candida growth was thematerial of prosthesis itself. 57% of the denture wearers showed growth of candidawhile 22% of subjects who had their own dentitions showed candida growth that theprosthesis is the dominant etiological factors in candida growth other local factorsmust be considered.